Characteristics and freezability of Tharparkar bull semen - KEDIA, N K; TIWARI, R P; MISHRA, G K; POYAM, M R; PANDEY, A K; NAIR, A K; SAHASRABUDHE, S A (The Indian Journal of Animal Sciences, 2014)
The study was undertaken to know the characteristics of various attributes of ejaculates collected from 6 elite pure Tharparkar bulls using artificial vagina in fresh and cryopreserved semen. The mean values for fresh seminal parameters, viz. seminal volume (ml), mass motility (0–5 scale), sperm concentration (millions/ml), individual motility (%), live sperm (%), intact acrosome (%), total sperm abnormalities (%), hypo osmotic swelling test (HOST -%) and cervical mucus penetration test (CMPT – mm) were 4.40 ± 0.24, 3.15 ± 0.12, 995.16 ± 70.99, 71.88 ± 0.99, 67.23± 1.08, 79.65 ± 1.21, 19.87± 0.54, 60.15 ± 1.76 and 31.56 ± 0.96, respectively. Semen volume and sperm concentration significantly differed between bulls within breed. The semen was cryopreserved after extension maintaining 20 million sperm/ straw, filling and sealing in 0.25 ml straw using programmable bio- freezer (IMV). Cryopreserved semen was assessed after 24 h freezing after thawing. Freezing significantly lowered motility (71.88 ± 0.99 vs 51.16 ± 1.08), intact acrosome (79.65 ± 1.21 vs 72.43 ± 1.42), HOST (60.15 ±1.76 vs 55.81 ±1.72) and CMPT (31.56 ± 0.96 vs 26.90 ± 0.91). Significantly higher percentages of sperm abnormalities (19.87 ± 0.54 vs 23.50 ± 0.82) were observed after freezing. Freezing resulted in significant decline in post thaw motility, acrosomal integrity, HOST and CMPT and increase in sperm abnormalities in Tharparkar bull semen.